KARAKTERISTIK KIMIA ROTI TEPUNG BERAS DENGAN TAMBAHAN ENZIM TRANSGLUTAMINASE - Ani Nuraisyah, Sapta Raharja, dan Faqih Udin (Jurnal Teknologi Industri Pertanian, 2018)
The effect of crosslinking by transglutaminase in rice flour was done to improve the characteristics of rice bread. The aims of this research was to obtain the optimum treatment of the combination of enzyme concentration and the substrate protein concentration of glutamine in gluten and lysine in skim milk so that the bread that is expected to produce a product that has the characteristics of a good and accepted by society. Theresponsse surface methodology (RSM) with central composite design (CCD) was used to obtain mathematical model in order to define correlation to any effected variables. Chemical characteristics have been observed from rice bread products. Based on the analysis of the two factor variables (concentration of transglutaminase enzyme and protein concentration) and four responsse parameters, namely moisture content, ash content, fat content, and protein content. The optimum solution suggested by Design expert 7.0.0 program for chemical characteristic responsse was 45% protein concentration and 4 U/g enzyme concentration with a desirability value of 0.518. Validation test of chemical characteristics of the rice bread are moisture content of 37.56%, ash content 1.75%, fat content 0.40%, and protein content 12.63%. Rice bread produced in the research has fulfilled the quality requirements for bread based on SNI No. 01-3840-1995 namely maximum moisture content of 40% (b/b) and maximum ash content of 1% (b/b).Keywords: gluten, RSM, skim milk, rice flour, transglutaminase enzyme